2021
DOI: 10.3390/toxins13080549
|View full text |Cite
|
Sign up to set email alerts
|

The Dragon’s Paralysing Spell: Evidence of Sodium and Calcium Ion Channel Binding Neurotoxins in Helodermatid and Varanid Lizard Venoms

Abstract: Bites from helodermatid lizards can cause pain, paresthesia, paralysis, and tachycardia, as well as other symptoms consistent with neurotoxicity. Furthermore, in vitro studies have shown that Heloderma horridum venom inhibits ion flux and blocks the electrical stimulation of skeletal muscles. Helodermatids have long been considered the only venomous lizards, but a large body of robust evidence has demonstrated venom to be a basal trait of Anguimorpha. This clade includes varanid lizards, whose bites have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 75 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…Addressing this knowledge gap through focused future research remains imperative for a comprehensive appreciation of these intricate evolutionary processes. In addition to further work investigating varanid lizard resistance to other venomous animals (whether as predators or prey), future work should also investigate the resistance of Anguimorph lizards to their own venoms, including presynaptic ion-channel toxins [ 49 ], and toxins that act upon the blood clotting cascade [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing this knowledge gap through focused future research remains imperative for a comprehensive appreciation of these intricate evolutionary processes. In addition to further work investigating varanid lizard resistance to other venomous animals (whether as predators or prey), future work should also investigate the resistance of Anguimorph lizards to their own venoms, including presynaptic ion-channel toxins [ 49 ], and toxins that act upon the blood clotting cascade [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…BLI based on nAChR mimotopes has been highly successful ( Harris et al, 2020a ; Harris et al, 2020b ; Harris et al, 2020c ; Harris et al, 2020d ; Youngman et al, 2021 ), but other ion channel receptor domains have been tested in preliminary experiments, including domain IV Ca V 1.2 ( Harris et al, 2021b ) and domain IV Na V 1.4 ( Dobson et al, 2021 ). Further investigations are needed to confirm the initial results.…”
Section: Methods To Study the Function Of Venomsmentioning
confidence: 99%
“…BLI has allowed the binding of crude venoms rich in α-neurotoxins to be investigated by the assessment of taxon-specific representative sequences across a range of prey (amphibian, mammalian, and reptilian). Prey-specific targeting of taxon-specific mimotopes has been assessed in snakes ( Harris et al, 2020a ; Harris et al, 2020b ; Harris et al, 2020c ; Youngman et al, 2021 ), lizards ( Dobson et al, 2021 ), and even fish ( Harris et al, 2021b ). All these studies provided insight into the biochemistry and evolution of venoms.…”
Section: Methods To Study the Function Of Venomsmentioning
confidence: 99%
“…The venom gland transcriptome analysis from H. horridum horridum revealed the presence of metalloproteases, lipases, vespryns, waspryns, lectins, cystatins and serine peptidase inhibitors, but none of these proteins were actually isolated from the venom [71]. Furthermore, Heloderma contains neurotoxins in its venom, and these toxins are able to bind sodium and calcium channels [72]. An important work by Fry et al [73] evaluated phylogeny between snakes and lizards and demonstrated that the venom delivery system of these animals could have evolved from the same common ancestor.…”
Section: Lizardsmentioning
confidence: 99%
“…Venoms from different species of the Varanus genus were evaluated for the ability to prevent blood clotting by thromboelastography, and the venoms differ regarding the activity; the most potent effects were found in arboricole species, probably due to the selective pressure, according to the authors [75]. Similar to Heloderma, Varanid lizards possess neurotoxins that are able to bind sodium and calcium channels [72].…”
Section: Lizardsmentioning
confidence: 99%